Measurement of dijet angular distributions and search for quark compositeness - Abbott, B; Abolins, M; Acharya, B; Adam, I; Adams, D; Adams, M; Ahn, S; Aihara, H; Alves, G; Amidi, E; Amos, N; Anderson, E; et al. (1998)
We have measured the dijet angular distribution in √s = 1.8 TeV pp̄ collisions using the D0 detector. Order αs3 QCD predictions are in good agreement with the data. At 95% confidence limit the data exclude models of quark compositeness in which the contact interaction scale is below 2 TeV.